Non-quenched and tempered steel wire with improved workability and toughness and method for manufacturing same
By controlling the alloy element composition and microstructure of non-tempered steel, AlN and MnS grains are formed, the problem of insufficient toughness and processability of non-tempered steel is solved, and high toughness and processability without heat treatment is achieved. It is suitable for in automobile or mechanical parts.
Patent Information
- Application Number
- CN202380040667.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2024-12-27
AI Technical Summary
The toughness of non-temperature steel is poor and difficult to meet the needs of automotive or mechanical components that require high toughness and machinability, and existing methods can lead to reduced toughness when improving machinability by adding S.
By controlling the alloy element composition and microstructure of non-tempered steel, especially adding high contents of S and N, AlN nitride and MnS grains, refining pearlite layers and ferrite grains, satisfying specific Mn /S, Al/N, Mn+Cr and C/Mn ratios achieve high toughness and processability without heat treatment.
The tensile strength of 700MPa or higher, the yield strength of 350MPa to 500MPa, the impact toughness of 60J/cm2 or greater and the tensile strength of 45000MPa·J/cm2 or greater and the product of tensile strength of × impact toughness of 45000MPa·J/cm2 or greater were obtained, which is suitable for high toughness and Processable automotive or mechanical components.
Smart Images

Figure BDA0005135758730000111 
Figure BDA0005135758730000121 
Figure BDA0005135758730000122
Abstract
Description
Technical Field
[0001] The present disclosure relates to a non-quenched and tempered steel wire having excellent workability and impact toughness and a method for producing the same, and more particularly, to a non-quenched and tempered steel wire suitable for use as a material for automobile or machine parts and a method for producing the same. Background Art
[0002] Unlike quenched and tempered steel that obtains a certain level of strength and toughness through quenching and tempering (QT) heat treatment, the QT heat treatment process is omitted in non-quenched and tempered steel. Therefore, non-quenched and tempered steel is economically advantageous not only by reducing heat treatment costs, simplifying processes to shorten delivery time, and improving productivity, but also by reducing CO generated by operating furnaces during heat treatment. 2 It is environmentally friendly. At the beginning of development, non-quenched and tempered steel was only applied to parts that did not require high toughness due to its relatively poor toughness compared to that of quenched and tempered steel. However, with the recent increase in demand for environmental feasibility and cost reduction, the demand for improving the toughness of non-quenched and tempered steel has increased. In addition, since cutting processes are often performed to obtain the final shape of the parts, machinability is also required. Generally, a large amount of MnS is generated by adding S to improve machinability, resulting in a problem of reduced toughness of the product. Summary of the invention
[0003] Technical issues
[0004] One aspect of the present disclosure provides a non-quenched and tempered steel wire having improved workability and impact toughness by improving toughness inferior to that of conventional quenched and tempered steel and by adding high contents of S and N without additional heat treatment, and a method for manufacturing the same.
[0005] Technical Solution
[0006] A non-quenched and tempered steel wire rod with improved workability and impact toughness according to one embodiment of the present disclosure includes, by weight percentage (wt%), 0.3% to 0.5% C, 0.4% to 0.9% Si, 0.5% to 1.2% Mn, 0.02% or less P, 0.01% to 0.05% S, 0.015% to 0.05% soluble Al, 0.1% to 0.3% Cr, 0.007% to 0.02% N, and the remainder including Fe and inevitable impurities, wherein the microstructure includes ferrite and pearlite, and the average thickness of the pearlite layer in the L cross section which is a cross section parallel to the rolling direction is 30 μm or less.
[0007] According to one embodiment of the present disclosure, in a non-quenched and tempered steel wire rod, an average grain size of ferrite in a C-section that is a section perpendicular to a rolling direction may be 20 μm or less.
[0008] According to one embodiment of the present disclosure, a non-quenched and tempered steel wire rod satisfies the following Relational Expression 1.
[0009] [Relational expression 1] 20≤Mn / S≤70
[0010] According to one embodiment of the present disclosure, the non-quenched and tempered steel wire rod satisfies the following Relational Expression 2.
[0011] [Relational Expression 2] 1.4≤Al / N≤7
[0012] According to one embodiment of the present disclosure, the non-quenched and tempered steel wire rod satisfies the following relational expression 3.
[0013] [Relational Expression 3] 0.7≤Mn+Cr≤1.4
[0014] According to one embodiment of the present disclosure, the non-quenched and tempered steel wire rod satisfies the following relational expression 4.
[0015] [Relational Expression 4] 0.2 ≤ C / Mn ≤ 0.7
[0016] According to one embodiment of the present disclosure, the non-quenched and tempered steel wire rod satisfies the following relational expression 5.
[0017] [Relational expression 5] 0≤Mn c / Mn f ≤3
[0018] (Mn c represents the average content (atomic %) of Mn contained in cementite in pearlite, and Mn f represents the average content (atomic %) of Mn contained in ferrite in pearlite.
[0019] According to one embodiment of the present disclosure, the non-quenched and tempered steel wire may have a tensile strength of 700 MPa or more and a yield strength of 350 MPa to 500 MPa. In addition, the yield strength ratio (yield strength / tensile strength) may be in the range of 0.45 to 0.65, and the room temperature impact toughness may be 60 J / cm 2 or greater, and the product of tensile strength and impact toughness can be 45000MPa·J / cm 2 or larger.
[0020] A method for manufacturing a non-quenched and tempered steel wire rod having improved workability and impact toughness according to an embodiment of the present disclosure includes: reheating a steel piece at a temperature range of 950° C. to 1100° C., the steel piece comprising, by weight percentage (wt%), 0.3% to 0.5% C, 0.4% to 0.9% Si, 0.5% to 1.2% Mn, 0.02% or less P, 0.01% to 0.05% S, 0.015% to 0.05% soluble Al, 0.1% to 0.3% Cr, 0.007% to 0.02% N, and the remainder containing Fe and inevitable impurities; finishing rolling the reheated steel piece at a temperature of 750° C. to 850° C. into a steel wire rod; coiling and cooling the steel wire rod,
[0021] The cooling performed after coiling includes: a first cooling process performed from a finishing temperature to a coiling temperature at an average cooling rate of 5°C / sec to 100°C / sec; a second cooling process performed from the coiling temperature to 700°C at an average cooling rate of 2°C / sec to 5°C / sec after the first cooling process; and a third cooling process performed from 700°C to 450°C at an average cooling rate of 0.1°C / sec to 2°C / sec after the second cooling process, wherein the microstructure of the steel wire rod contains ferrite and pearlite, and the average thickness of the pearlite layer in the L cross section which is a cross section parallel to the rolling direction is 30 μm or less.
[0022] Beneficial Effects
[0023] In the non-quenched and tempered steel wire rod with improved workability and impact toughness according to one embodiment of the present disclosure, Al is combined with N to form AlN nitrides that suppress grain boundary growth during heating, thereby reducing the thickness of the pearlite layer and refining the grains of ferrite to improve impact toughness. In addition, by refining the MnS grains by controlling the Mn / S ratio, workability can be improved while minimizing the deterioration of impact toughness. Therefore, the steel wire rod can be applied to materials for automobiles or machine parts that require both workability and impact toughness even when heat treatment is omitted. DETAILED DESCRIPTION
[0024] A non-quenched and tempered steel wire rod with improved workability and impact toughness according to one embodiment of the present disclosure includes, by weight percentage (wt%), 0.3% to 0.5% C, 0.4% to 0.9% Si, 0.5% to 1.2% Mn, 0.02% or less P, 0.01% to 0.05% S, 0.015% to 0.05% soluble Al, 0.1% to 0.3% Cr, 0.007% to 0.02% N, and the remainder including Fe and inevitable impurities, wherein the microstructure includes ferrite and pearlite, and the average thickness of the pearlite layer in the L cross section which is a cross section parallel to the rolling direction is 30 μm or less.
[0025] Embodiments of the invention
[0026] This specification does not describe all the elements of the embodiments of the present disclosure, and a detailed description of what is known in the art or a redundant description of substantially the same configuration can be omitted. In addition, unless otherwise stated, the term "comprising" an element does not exclude other elements, but may also include other elements. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. Hereinafter, the reason for numerically limiting the content of alloying elements in the embodiments of the present disclosure will be described. Hereinafter, the present disclosure will be described in detail.
[0027] The present inventors have studied a method for providing a steel wire having workability and impact toughness from various viewpoints, and have found that workability and impact toughness can be obtained by appropriately controlling the composition of alloy elements and microstructure of the steel wire without additional heat treatment, thereby completing the present disclosure.
[0028] A non-quenched and tempered steel wire rod with improved workability and impact toughness according to one embodiment of the present disclosure comprises, by weight percentage (wt%), 0.3% to 0.5% C, 0.4% to 0.9% Si, 0.5% to 1.2% Mn, 0.02% or less P, 0.01% to 0.05% S, 0.015% to 0.05% soluble Al, 0.1% to 0.3% Cr, 0.007% to 0.02% N, and the remainder comprising Fe and inevitable impurities, wherein the microstructure comprises ferrite and pearlite, and the average thickness of the pearlite layer in the L cross section which is a cross section parallel to the rolling direction is 30 μm or less. Hereinafter, unless otherwise specified, the unit is wt%.
[0029] The C content is 0.3% to 0.5%.
[0030] Carbon (C) is an element for improving the strength of the steel wire rod. In order to obtain the above-mentioned effect, C is preferably contained in an amount of 0.3% or more. However, an excessive C content may deteriorate toughness and workability, and thus the upper limit of the C content may be controlled to 0.5%.
[0031] The content of Si is 0.4% to 0.9%.
[0032] Silicon (Si) is an element effective as a deoxidizer for improving strength. When the Si content is less than 0.4%, the above effect cannot be obtained. When the Si content exceeds 0.9%, the deformation resistance of the steel increases rapidly due to solid solution strengthening, and therefore the upper limit of the Si content can be controlled to 0.9%.
[0033] The content of Mn is 0.5% to 1.2%.
[0034] Manganese (Mn) is an element effective as a deoxidizer and a desulfurizer. When the Mn content is less than 0.5%, the above effects may not be obtained. When the Mn content exceeds 1.2%, the strength of the steel is excessively increased so that the deformation resistance of the steel is rapidly increased, resulting in deterioration of cold workability, and therefore, the upper limit of the Mn content can be controlled to 1.2%.
[0035] The content of P is 0.02% or less.
[0036] Phosphorus (P), as an impurity inevitably contained in steel, is a main contributing element to deterioration of toughness and reduction in delayed fracture resistance by segregating into grain boundaries. Therefore, it is preferable to control the P content as low as possible. Theoretically, it is preferable to control the P content to 0%, but P is inevitably contained during the manufacturing process. Therefore, it is important to control the upper limit, and in the present disclosure, the upper limit of the P content can be controlled to 0.02%.
[0037] The content of S is 0.01% to 0.05%.
[0038] Sulfur (S), as a main causative element that causes significant deterioration of the ductility of steel due to segregation into grain boundaries and deterioration of delayed fracture resistance and stress relaxation due to formation of emulsions in steel, is an impurity that is inevitably contained in steel during the manufacturing process. However, as in the present disclosure, S can be actively used to improve workability. Since S combines with Mn to form MnS that improves workability, considering that the S content is effective for improving workability without significantly impairing the toughness of steel, the S content is controlled within the range of 0.01% to 0.05% in the present disclosure.
[0039] The content of soluble Al is 0.015% to 0.05%.
[0040] Soluble Al is an element effective as a deoxidizer. Soluble Al may be contained in an amount of 0.015% to obtain the above-mentioned effect. However, in the case where the Al content exceeds 0.05%, difficulties may occur during the manufacturing process due to Al oxides generated during the casting process. Therefore, in the present disclosure, the upper limit of the Al content may be controlled to 0.05%.
[0041] The content of Cr is 0.1% to 0.3%.
[0042] Chromium (Cr) is an element for promoting the transformation of ferrite and pearlite during hot rolling. In addition, Cr does not increase the strength of steel too much, reduces the amount of solid solution of C by precipitating carbides, and helps to reduce dynamic deformation aging caused by solid solution of carbon. In the case where the Cr content is less than 0.1%, the above effect may not be obtained, and in the case where the C content exceeds 0.3%, the strength of the steel is excessively increased to rapidly increase the deformation resistance of the steel, resulting in deterioration of cold workability. Therefore, the upper limit of the Cr content can be controlled to 0.3%.
[0043] The content of N is 0.007% to 0.02%.
[0044] N is an essential element for achieving the effect of improving impact toughness by reducing the grain size through the formation of nitrides with Al. In the case where the N content is less than 0.007%, it is difficult to obtain a sufficient amount of nitrides, resulting in a reduction in the production of AlN precipitates, and the toughness desired in the present disclosure cannot be obtained. In the case where the N content exceeds 0.02%, the solid solution of N that does not exist as a nitride increases to deteriorate the toughness and ductility of the steel wire. Therefore, in the present disclosure, the upper limit of the N content can be controlled to 0.02%.
[0045] The remaining component of the non-quenched and tempered steel wire of the present disclosure is iron (Fe). However, the non-quenched and tempered steel wire may contain other impurities incorporated during the common industrial manufacturing process of steel. Since impurities are known to any technician in the manufacturing field, no specific mention of impurities is made in the present disclosure.
[0046] The non-quenched and tempered steel wire according to one embodiment of the present disclosure contains ferrite and pearlite as microstructures, and the average thickness of the pearlite layer in the L cross section which is a cross section parallel to the rolling direction may be 30 μm or less. In the case where the thickness of the pearlite exceeds 30 μm and a coarse pearlite band is formed, the total interface between ferrite and pearlite is reduced and the impact energy may not be distributed, so that cracks are easily extended and the impact toughness is reduced.
[0047] In the non-quenched and tempered steel wire rod according to one embodiment of the present disclosure, the average grain size of ferrite in the C section which is a section perpendicular to the rolling direction may be 20 μm or less. By finely adjusting the grain size of ferrite, impact toughness can be obtained.
[0048] The non-quenched and tempered steel wire according to one embodiment of the present disclosure may satisfy relational expressions 1 to 5. In relational expressions 1 to 4, [Al], [N], [C], [S], [Mn], and [Si] respectively represent the contents (weight %) of the elements.
[0049] [Relational Expression 1] 20≤Mn / S≤70 (machinability)
[0050] Relational expression 1 is an expression related to machinability. According to the present disclosure, MnS is formed by adding high contents of S and Mn. MnS, as an elongated inclusion, has an elongated shape and orientation in the rolling direction, and significantly improves the machinability of the non-quenched and tempered steel wire rod of the present disclosure. However, when an impact is applied thereto, MnS acts as the starting point of the crack and its expansion path, thereby deteriorating the impact toughness. When the Mn / S ratio is less than 20, machinability can be met, but impact toughness may be deteriorated. When the Mn / S ratio exceeds 70, machinability may be insufficient. Therefore, in the present disclosure, the Mn / S ratio can be controlled to 20 to 70.
[0051] [Relational Expression 2] 1.4≤[Al] / [N]≤7 (impact toughness)
[0052] Relational expression 2 is a relational expression related to toughness. According to the present disclosure, AlN is formed by adding high contents of N and Al. The precipitation of fine AlN in the steel refines the grains, thereby improving the impact toughness of the non-quenched and tempered steel wire according to the present disclosure. In order to express the above-mentioned effect, it is preferred to form as many AlN precipitates as possible with a size of 50 nm or less, and for this purpose, it is preferred to control the Al / N ratio within the range of 1.4 to 7. When the Al / N ratio is less than 1.4, AlN precipitates cannot be fully formed, and when the Al / N ratio exceeds 7, coarse AlN precipitates are formed, which leads to deterioration of impact toughness. Therefore, in the present disclosure, the Al / N ratio can be controlled within the range of 1.4 to 7, preferably 1.9 to 5.0, and more preferably 3.5 to 5.0.
[0053] [Relational Expression 3] 0.7≤Mn+Cr≤1.4 (impact toughness)
[0054] Relational expression 3 is an expression related to impact toughness. Mn and Cr refine the interlayer spacing of pearlite, thereby having the effect of improving toughness. When the sum of Mn and Cr is 0.7 or more, this effect is fully obtained. However, when the sum of Mn and Cr exceeds 1.4, the fraction of pearlite increases, resulting in excessive increase in strength, causing deterioration in impact toughness. Therefore, in the present disclosure, the sum of Mn and Cr is controlled within the range of 0.7 to 1.4, preferably 0.8 to 1.3, and more preferably 1.0 to 1.3.
[0055] [Relational Expression 4] 0.2≤C / Mn≤0.7 (impact toughness)
[0056] Relational expression 4 is an expression related to impact toughness. When the C / Mn ratio is less than 0.2, a hard structure (such as martensite or bainite) with low toughness is likely to be formed, resulting in deterioration of impact toughness. On the contrary, when the C / Mn ratio exceeds 0.7, the amount of pearlite with a wide interlamellar spacing increases, resulting in deterioration of impact toughness. Therefore, the C / Mn ratio is controlled within the range of 0.2 to 0.7, preferably 0.3 to 0.6, and more preferably 0.4 to 0.5.
[0057] [Relational expression 5] 0≤Mn c / Mn f ≤3(cold workability)
[0058] Here, Mn c represents the average content (atomic %) of Mn contained in cementite in pearlite, and Mn f It shows the average content (atomic %) of Mn contained in ferrite in pearlite.
[0059] Relational expression 5 is an expression related to cold workability, and represents the Mn distribution ratio in pearlite. The Mn distribution ratio in pearlite is a value obtained by dividing the average content (atomic %) of Mn contained in cementite in pearlite by the average content (atomic %) of Mn contained in ferrite in pearlite. In the present disclosure, the Mn distribution ratio in pearlite is controlled within the range of 0 to 3. The inventors have confirmed through a large number of experiments that when the Mn distribution ratio in pearlite satisfies 3 or less, cold workability is improved, thereby completing the present disclosure. Since Mn is an element with a strong tendency to segregate into cementite in pearlite, the Mn distribution ratio of common pearlite is 5 or more. According to the present disclosure, in order to control the Mn distribution ratio to 3 or less, the distribution of Mn into cementite in pearlite should be suppressed, and the Mn distribution ratio in pearlite can be achieved by a cooling process of applying different cooling rates to different temperature sections respectively after the winding process.
[0060] In addition, the tensile strength of the non-quenched and tempered steel material according to one embodiment of the present disclosure may be 700 MPa or more.
[0061] In addition, the yield strength of the non-quenched and tempered steel material according to one embodiment of the present disclosure may be 350 MPa to 500 MPa.
[0062] In addition, the non-quenched and tempered steel material according to one embodiment of the present disclosure may have a yield ratio of 0.45 to 0.65.
[0063] In addition, the impact toughness of the non-quenched and tempered steel material according to one embodiment of the present disclosure may be 60 J / cm 2 or larger.
[0064] In addition, the product of the tensile strength and impact toughness of the non-quenched and tempered steel material according to one embodiment of the present disclosure may be 45000 MPa·J / cm 2 or larger.
[0065] Hereinafter, a method for manufacturing a non-quenched and tempered steel wire rod according to one embodiment of the present disclosure will be described.
[0066] A method for manufacturing a non-quenched and tempered steel wire having improved workability and impact toughness according to an embodiment of the present disclosure includes: reheating a steel piece at a temperature range of 950° C. to 1100° C., the steel piece comprising, by weight percentage (wt%), 0.3% to 0.5% C, 0.4% to 0.9% Si, 0.5% to 1.2% Mn, 0.02% or less P, 0.01% to 0.05% S, 0.015% to 0.05% soluble Al, 0.1% to 0.3% Cr , 0.007% to 0.02% N, and the remainder containing Fe and inevitable impurities; finish rolling the reheated steel piece at a temperature of 750°C to 850°C into a steel wire rod; and coiling and cooling the steel wire rod, wherein the cooling performed after coiling includes: a first cooling process performed from the finishing temperature to the coiling temperature at an average cooling rate of 5°C / sec to 100°C / sec; and a second cooling process performed from the coiling temperature to 700°C at an average cooling rate of 2°C / sec to 5°C / sec after the first cooling process; and
[0067] a third cooling process performed from 700° C. to 450° C. at an average cooling rate of 0.1° C. / sec to 2° C. / sec after the second cooling process,
[0068] The microstructure of the steel wire rod includes ferrite and pearlite, and the average thickness of the pearlite layer in the L cross section which is a cross section parallel to the rolling direction is 30 μm or less.
[0069] Furthermore, according to one embodiment of the present disclosure, the average grain size of ferrite in a C-section which is a section perpendicular to the rolling direction is 20 μm or less.
[0070] Furthermore, according to one embodiment of the present disclosure, the following relational expression 1 may be satisfied.
[0071] [Relational expression 1] 20≤Mn / S≤70
[0072] Furthermore, according to one embodiment of the present disclosure, the following relational expression 2 may be satisfied.
[0073] [Relational Expression 2] 1.4≤Al / N≤7
[0074] Furthermore, according to one embodiment of the present disclosure, the following relational expression 3 may be satisfied.
[0075] [Relational Expression 3] 0.7≤Mn+Cr≤1.4
[0076] Furthermore, according to one embodiment of the present disclosure, the following relational expression 4 may be satisfied.
[0077] [Relational Expression 4] 0.2 ≤ C / Mn ≤ 0.7
[0078] Furthermore, according to one embodiment of the present disclosure, the following relational expression 5 may be satisfied.
[0079] [Relational expression 5] 0≤Mn c / Mn f ≤3
[0080] Hereinafter, each process of the manufacturing method will be described in more detail.
[0081] First, a bloom satisfying the above alloy element composition may be heated and rolled into a billet.
[0082] Reheating process
[0083] The reheating process, as a process of reheating the rolled billet, is a process for reducing the rolling load when rolling the steel wire rod. In this regard, the reheating process can be performed in a temperature range of 950°C to 1,100°C. At a reheating temperature below 950°C, the rolling load may increase, causing difficulties in the manufacturing method. On the contrary, at a reheating temperature above 1,100°C, AlN formed in the steel piece turns into a solid solution again during heating, so that the grain refinement effect caused by AlN may be significantly reduced.
[0084] The process of rolling steel wire
[0085] In the process of rolling the steel wire rod, the reheated steel piece is hot rolled into the steel wire rod. In this case, the finishing temperature of the hot rolling may be 750° C. to 850° C. At a finishing temperature below 750° C., the rolling load may increase, and at a finishing temperature above 850° C., the grains may coarsen, so that the high toughness desired in the present disclosure may not be obtained.
[0086] Winding process
[0087] A process of winding the steel wire manufactured as described above in the shape of a coil may be performed. In this case, the coiling temperature may be 750°C to 850°C. Since the temperature of the steel wire obtained by finish rolling may be increased due to transformation heating, the temperature of the steel wire immediately before coiling may be higher than the final rolling temperature. In this case, according to the temperature increased by heating, the steel wire may be coiled after being cooled to the coiling temperature, or may be coiled without an additional cooling process. At a coiling temperature below 750°C, the martensite generated in the surface layer during cooling cannot be recovered due to double rows, and tempered martensite is formed, resulting in a problem of increasing the possibility of inducing surface defects during the drawing process. On the contrary, at a coiling temperature above 850°C, a thick scale may be formed on the surface of the steel wire, so that surface defects may easily occur during the removal of the scale, and productivity may deteriorate due to the increase in cooling time in the subsequent cooling process.
[0088] Cooling process
[0089] The cooling process, as a process of obtaining the non-quenched and tempered steel wire rod according to the present disclosure by cooling the steel wire rod after final rolling and coiling, is a process of controlling the distribution ratio of Mn contained in the cementite and ferrite in the pearlite mentioned above. In order to control the Mn distribution ratio of cementite in pearlite to 3 or less, it is necessary to suppress the distribution of Mn as much as possible during the cooling process. In order to suppress the distribution of Mn into cementite as much as possible, it is effective to apply different cooling rates to different temperature sections.
[0090] First cooling process (CR1): final rolling temperature to coiling temperature
[0091] The first cooling process may be performed at an average cooling rate of 5°C / sec to 100°C / sec from the finishing rolling temperature to the coiling temperature. Since Mn diffuses very rapidly in the temperature section of the first cooling process, at a cooling rate lower than 5°C / sec, the possibility of the Mn distribution ratio exceeding 3 is high, and it is difficult to commercially apply a cooling rate higher than 100°C / sec. Therefore, the first cooling process may be performed at a cooling rate of 5°C / sec to 100°C / sec.
[0092] Second cooling process (CR2): coiling temperature to 700°C
[0093] The second cooling process may be performed after the first cooling process at an average cooling rate of 2°C / sec to 5°C / sec from the coiling temperature to 700°C. At a cooling rate lower than 2°C / sec, the Mn distribution ratio may exceed 3 due to diffusion of Mn, and at a cooling rate higher than 5°C / sec, an inhomogeneous material (e.g., a mixed material) may be obtained due to inhomogeneous cooling. Therefore, the second cooling process may be performed at a cooling rate of 2°C / sec to 5°C / sec.
[0094] Third cooling process (CR3): 700℃ to 450℃
[0095] The third cooling process may be performed from 700°C to 450°C at an average cooling rate of 0.1°C / sec to 2°C / sec after the second cooling process. At a cooling rate lower than 0.1°C / sec, the interlamellar spacing of pearlite is coarsened, making it difficult to obtain the strength desired in the present disclosure, while at a cooling rate higher than 2°C / sec, a low-temperature bainite structure may be formed during cooling. Therefore, the third cooling process may be performed at a cooling rate of 0.1°C / sec to 2°C / sec.
[0096] Hereinafter, the present disclosure will be described in more detail by way of examples. However, it should be noted that the following examples are only intended to illustrate the present disclosure in more detail and are not intended to limit the scope of the present disclosure. This is because the scope of the present disclosure is determined by the matters described in the claims and can be reasonably inferred therefrom.
[0097] Example
[0098] Each bloom having the alloy element composition shown in Table 1 was heated at 1,200°C for 4 hours and rolled into a billet at a finishing temperature of 1,100°C. Then, the billet was heated at 1,100°C for 90 minutes and hot rolled into a steel wire rod at a finishing temperature of 800°C using a 25 mm roll. Subsequently, a three-step cooling process including a CR1-CR2-CR3 temperature section was applied thereto to manufacture steel wire rod specimens of Examples 1 to 7 and Comparative Examples 1 to 13. Then, the microstructure and the Mn distribution ratio of ferrite / cementite of the cooled steel wire rod specimens are shown in Table 2 below, and the tensile strength and impact toughness properties thereof were measured and shown in Table 3 below.
[0099] Here, room temperature tensile strength was measured at the center of a non-quenched and tempered steel specimen at 25°C, and room temperature impact toughness of a specimen having a U-notch (based on a standard specimen, 10×10×55 mm) was measured at 25°C using a Charpy impact energy value obtained by a Charpy impact test.
[0100] In addition, in order to evaluate the machinability, a steel wire rod having a diameter of 26 mm was processed into a cold drawn bar (CD-bar) having a diameter of 24 mm at a reduction rate of 14.8%. The machinability was evaluated by using a CNC lathe, and the fragility of the turning chips was evaluated after the turning operation was performed until the diameter of 24 mm of the CD-bar was reduced to a diameter of 15 mm. In this case, cutting was performed under the conditions of a cutting rate of 100 mm / min, a feed rate of 0.1 mm / rev, and a cutting depth of 1.0 mm by using cutting oil. The fragility of the chips was evaluated based on the number of chips generated during the turning process, 5 or less chips were evaluated as good, more than 5 but not more than 10 chips were evaluated as average, and more than 10 chips were evaluated as poor, and the results are shown in Table 3.
[0101] Furthermore, the average thickness of the pearlite layer was obtained by calculating the arithmetic mean from 30 images obtained at a point corresponding to a quarter diameter of the steel wire rod at 200× magnification, and the average grain size of ferrite refers to a value corresponding to an equivalent circle diameter.
[0102] [Table 1]
[0103]
[0104] [Table 2]
[0105]
[0106] [Table 3]
[0107]
[0108]
[0109] Specifically, the steel wires of Examples 1 to 7 satisfying all chemical compositions, relational expressions, and manufacturing conditions provided in the present disclosure satisfy a tensile strength of 700 MPa or more, a strength of 60 J / cm 2 or higher room temperature impact toughness and 45000MPa·J / cm 2 or greater tensile strength × impact toughness value and workability. In contrast, the steel wires of Comparative Examples 1 to 5 outside the chemical composition may not satisfy one or more values. Although Comparative Examples 6 to 9 satisfy the chemical composition suggested by the present disclosure, the values of the relational expressions are outside the suggested values, making it impossible to achieve the desired physical properties herein. In addition, in the case of Comparative Examples 10 to 13 that do not satisfy the heating temperature and cooling conditions among the manufacturing conditions, both the target tensile strength and impact toughness cannot be satisfied.
[0110] Industrial Applicability
[0111] According to the present disclosure, a non-quenched and tempered steel wire rod having excellent workability and impact toughness can be obtained without additional heat treatment, and thus the present disclosure has industrial applicability.
Claims
1. A non-quenched and tempered steel wire rod having improved workability and impact toughness, comprising, by weight percentage (wt%), 0.3% to 0.5% of C, 0.4% to 0.9% of Si, 0.5% to 1.2% of Mn, 0.02% or less of P, 0.01% to 0.05% of S, 0.015% to 0.05% of soluble Al, 0.1% to 0.3% of Cr, 0.007% to 0.02% of N, and the remainder comprising Fe and inevitable impurities, wherein the microstructure comprises ferrite and pearlite, and the average thickness of the pearlite layer in the L cross section which is a cross section parallel to the rolling direction is 30 μm or less. 2 . The non-heat-treated steel wire rod according to claim 1 , wherein an average grain size of ferrite in a C-section which is a section perpendicular to the rolling direction is 20 μm or less.
3. The non-quenched and tempered steel wire according to claim 1, wherein the following relational expression 1 is satisfied: [Relational expression 1]20≤Mn / S≤70.
4. The non-quenched and tempered steel wire according to claim 1, wherein the following relational expression 2 is satisfied: [Relational Expression 2]1.4≤Al / N≤7.
5. The non-quenched and tempered steel wire rod according to claim 1, wherein the following relational expression 3 is satisfied: [Relational expression 3]0.7≤Mn+Cr≤1.
4.
6. The non-quenched and tempered steel wire rod according to claim 1, wherein the following relational expression 4 is satisfied: [Relational Expression 4]0.2≤C / Mn≤0.
7.
7. The non-quenched and tempered steel wire rod according to claim 1, wherein the following relational expression 5 is satisfied: [Relational expression 5] 0≤Mn c / Mn f ≤3 (Mn c represents the average content (atomic %) of Mn contained in cementite in pearlite, and Mn f represents the average content (atomic %) of Mn contained in ferrite in pearlite.
8. The non-quenched and tempered steel wire rod according to claim 1, wherein the tensile strength is 700 MPa or more.
9. The non-quenched and tempered steel wire rod according to claim 1, wherein the yield strength is 350 MPa to 500 MPa.
10. The non-quenched and tempered steel wire rod according to claim 1, wherein the yield ratio is 0.45 to 0.
65.
11. The non-quenched and tempered steel wire according to claim 1, wherein the room temperature impact toughness is 60 J / cm 2 or larger.
12. The non-quenched and tempered steel wire according to claim 1, wherein the product of the tensile strength and the room temperature impact toughness is 45000 MPa·J / cm 2 or larger.
13. A method for producing a non-quenched and tempered steel wire having improved workability and impact toughness, the method comprising: reheating a steel piece at a temperature in the range of 950° C. to 1100° C., the steel piece comprising, by weight percentage (wt%), 0.3% to 0.5% C, 0.4% to 0.9% Si, 0.5% to 1.2% Mn, 0.02% or less P, 0.01% to 0.05% S, 0.015% to 0.05% soluble Al, 0.1% to 0.3% Cr, 0.007% to 0.02% N, and the remainder comprising Fe and inevitable impurities; Finish rolling the reheated steel piece at a temperature of 750° C. to 850° C. into a steel wire rod; as well as The steel wire is coiled and cooled, The cooling after the winding comprises: A first cooling process from the finishing temperature to the coiling temperature at an average cooling rate of 5°C / sec to 100°C / sec; a second cooling process performed from the coiling temperature to 700° C. at an average cooling rate of 2° C. / sec to 5° C. / sec after the first cooling process; and a third cooling process performed from 700° C. to 450° C. at an average cooling rate of 0.1° C. / sec to 2° C. / sec after the second cooling process, The microstructure of the steel wire rod includes ferrite and pearlite, and an average thickness of a pearlite layer in an L cross section which is a cross section parallel to a rolling direction is 30 μm or less. 14 . The method according to claim 13 , wherein an average grain size of ferrite in a C-section which is a section perpendicular to the rolling direction is 20 μm or less.
15. The method according to claim 13, wherein the following relational expression 1 is satisfied: [Relational expression 1]20≤Mn / S≤70.
16. The method according to claim 13, wherein the following relational expression 2 is satisfied: [Relational Expression 2]1.4≤Al / N≤7.
17. The method according to claim 13, wherein the following relational expression 3 is satisfied: [Relational expression 3]0.7≤Mn+Cr≤1.
4.
18. The method according to claim 13, wherein the following relational expression 4 is satisfied: [Relational Expression 4]0.2≤C / Mn≤0.
7.
19. The method according to claim 13, wherein the following relational expression 5 is satisfied: [Relational expression 5] 0≤Mn c / Mn f ≤3 (Mn c represents the average content (atomic %) of Mn contained in cementite in pearlite, and Mn f represents the average content (atomic %) of Mn contained in ferrite in pearlite.
20. The method of claim 13, wherein the coiling temperature is 750°C to 850°C.
